Influence of thermal post treatments on microstructure and oxidation behavior of EB-PBF manufactured Alloy 718 - Sadeghi, Esmaeil; Karimi, Paria; Momeni, Soroush; Seifi, Mohsen; Eklund, Anders; Andersson, Joel (Materials Characterization, 2019)
The effect of thermal post treatments consisting of heat treatment (HT), hot isostatic pressing (HIP), and combined HIP-HT on microstructure and oxidation behavior of Alloy 718 manufactured by electron beam powder bed fusion (EB-PBF) technique was investigated. Oxidation of the as-built and post-treated specimens was performed in ambient air at 650, 750, and 850 degrees C for up to 168 h. Directional columnar-grained microstructure, pores and fine Nb-rich carbides were observed in the as-built specimen. The HT specimen presented the columnar microstructure, plate-like delta phase at grain boundaries, and pores. The dominant grain crystallographic orientation was changed from <001> in the as-built specimen to <101> after HT. No grain boundary delta phase was observed in the HIPed specimen, but recrystallization occurred in both the HIP and HIP-HT specimens due to a rapid cooling after HIPing motivating the nucleation of fine grains with limited time to grow. After oxidation exposure at 650 and 750 degrees C for 168 h, no big difference between weight changes of the as-built and post-treated specimens was noted, whereas at 850 degrees C, the combined HIP-HT specimen showed the most promising corrosion resistance with the least weight change. At 850 degrees C, a protective scale of Cr2O3 rich in Cr, Ti, and Ni as well as an internal oxide (branched structure of alumina) developed in all the specimens, while, only a protective Cr2O3 scale was found at 650 and 750 degrees C. The HIP-HT specimen at 850 degrees C developed an oxide scale, which was denser and more adherent in comparison to the oxide scales formed on the other three specimens, associated with its limited defect distribution and more homogenized microstructure. Moreover, the S phase formed close to the surface of the exposed specimens during the oxidation exposure at 850 degrees C most probably led to nucleation and growth of the oxide scale.
CRIS-Team WoS Importer:2019-04-09